Islamic Education and Intercultural Competence: Promoting Religious Literacy in Multicultural Societies - Yahya Mohammed Abu Bakr; Norakyairee Mohd Raus; Ahmed H. Ibrahim; Atta Ullah Faizi (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study examines the role of Islamic education in promoting intercultural competence and religious literacy within increasingly multicultural societies. The research aims to explore the theoretical relationship between Islamic educational philosophy, intercultural competence, and religious literacy while identifying their potential contributions to social cohesion, inclusive citizenship, and peaceful coexistence. The study employs a qualitative library research approach using a systematic review of contemporary scholarly literature. Data were collected from peer-reviewed journal articles, academic books, policy reports, and international educational documents and analyzed through thematic content analysis to identify recurring concepts, emerging trends, and theoretical convergences. The findings indicate that Islamic education possesses substantial potential to foster intercultural competence through core principles such as ta‘āruf (mutual understanding), karāmah (human dignity), ‘adl (justice), raḥmah (compassion), and ta‘āwun (cooperation). The study further reveals that religious literacy and intercultural competence function as complementary educational objectives that strengthen empathy, critical thinking, ethical citizenship, social inclusion, and intercultural dialogue. The novelty of this research lies in the development of the Islamic Intercultural Religious Literacy Framework (IIRLF), an integrative conceptual model that synthesizes Islamic educational philosophy, intercultural competence theory, and religious literacy studies into a comprehensive framework for multicultural education. The study concludes that Islamic education can serve as a significant educational resource for preparing learners to engage responsibly and constructively in culturally and religiously diverse societies while maintaining strong ethical and spiritual foundations